Harnessing nitrous oxide in post-harvest management of fresh horticultural produce - BARMAN, KALYAN; SHARMA, SWATI; PATEL, V B; ASREY, RAM (The Indian Journal of Agricultural Sciences, 2016)
High post-harvest losses in fresh horticultural produce and the increasing apprehensions among the consumers for harmful chemical residues have made it imperative for researchers to find safe, novel and natural techniques to achieve augmentation in shelf-life without having any detrimental influence on human health. Nitrous oxide, commonly known as “Laughing gas” is a naturally occurring colourless and non-flammable atmospheric gas. In the recent past, several researchers have documented that nitrous oxide gas inhibits ethylene production as well as action in freshly harvested fruits and vegetables. It also exhibits high potential in inhibiting fungal growth and decay, consequently reducing post-harvest losses due to diseases. Owing to its non-toxic nature, nitrous oxide can be potentially used to delay ripening and senescence of fresh horticultural produce during post-harvest storage and to assure food safety. In the present review, we have mainly focused on various effects of nitrous oxide on postharvest decay, ethylene biosynthesis and its action, respiration and other physico-chemical attributes of fruits and vegetables. Post-harvest application of nitrous oxide may open up various opportunities for its commercial use to prolong storage and marketability of fresh horticultural produce.